Distribution of the Mindanao Spiky-helmed pygmy grasshopper misythus echinatus (Stal, 1877) (tetrigidae: cladonotini) - Patano, Romeo R. Jr.; Mohagan, Alma B.; Amoroso, Victor B. (2021)
"Misythus Stal, 1877 (Tetrigidae: Cladonotinae) is a diverse genus of pygmy grasshoppers with 27 species and two subspecies, all of which are endemic to the islands of the Philippines. Here, the emphasis is on the spiky wingless pygmy grasshopper, Misythus echinatus (Stal, 1877). The species is endemic to northern Mindanao and adjacent islands (Siargao Island, Bucas Island, Surigao, Iligan, and Butuan). The last published records originate from 1916 and most of the specimens hitherto reported lacked habitat descriptions and especially images of the species in its natural environment. In this study, we report the species for the first time from Bukidnon and Davao regions; we update its distribution in Mindanao and describe its natural habitat with supporting images. An updated distribution map for this species is provided, together with detailed measurements of male and female specimens, in order to make a comparison between different populations possible"-Title page.
Includes bibliographic references.
Keywords: Endemic animals; Upland ecology; Ultrabasic rocks